Board of directors and firm debt in Spanish SMEs: A power perspective - Juan Francisco Martín-Ugedo; Antonio Mínguez-Vera (European Research on Management and Business Economics (ERMBE), 2023)
This manuscript examines the influence of some variables relating to boards of directors that we consider to be proxies for power (gender diversity, duality, board size and insider ownership). Their influence on firm debt is explored. The sample examined, Spanish non-financial SMEs, has some particular characteristics. Share ownership, which is usually highly concentrated in the Civil Law context, is even more concentrated when we focus on SMEs. As a consequence, there is little separation between ownership and control. We have employed a power perspective as the main theoretical framework. Data were obtained from the SABI database, and the methodology employed is a panel data, applying the System GMM technique. This methodology makes it possible to control for endogeneity and individual heterogeneity. The results show that a larger proportion of female directors, larger boards, the separation of the roles of CEO and Chairman, and more shares owned by directors and by the CEO stimulate a decrease in firm debt. This evidence supports the hypotheses tested.
Keywords: G30; G32; 650; Board of directors; Power; Firm debt